The Current Industrial Relations Scene in Canada 1977 - Dion, Gérard (Relations industrielles / Industrial Relations, 1977)
This article reviews "The Current Industrial Relations Scene in Canada 1977" edited by H.D. Wood and Pradeep Kumar.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z